Analisa Tingkat Androgenitas pada Mahasiswa - Devi Setyaningsih, Natalia Regina (Jurnal Ilmiah Psyche, 2019)
This research aimed to measure the level of androgyny of Sanata Dharma University students. The subjects were 100 students of Sanata Dharma University consisted of men and women of age 18 to 22 years old participating the research. There search uses quantitative approach parallel with descriptive method. The only variable is androgyny, which composed of masculinity and femininity equally in one individual. The instrument to measure is Bem Sex Role Inventory which adopted to Indonesian language. The test was taken to measure the androgyny by descriptive analysis and gender roles division based on group median scores of masculine and feminine scale. The analysis has resulted in greater masculine mean empirical value than mean theoretical value {87,28 >73,5} which exposing higher average of the group than its average theoretical value, therefore means the subjects has the tendency of high masculinity. In addition, the analysis has resulted in larger feminine mean empirical value than its average theoretical value, consequently means the research subject has the tendency of high femininity {88,43 >70} which featuring higher average group value than its average theoretical, which means widely the research subject has the tendency of high femininity. All things considered, the gender roles division from 100 students have explained that 70% of them have androgyny gender roles, while other 30% have masculinity, femininity and or undifferentiated. Finally, the students of Sanata Dharma University aged of 18 to 22 years old mostly have gender roles of androgyny